Performance of mud crab farming in natural seed-based apartment systems with various pre-transportation holding durations - Atul Hayati, Mira; Effendi, Irzal; Hadiroseyani, Yani; Budiardi, Tatag (Jurnal Akuakultur Indonesia, 2025)
Farming mud crabs (Scylla serrata) in Indonesia generally use seeds from natural habitats, which are caught, held, and transported dry to the farming location. The crabs are held for several days while waiting for consumers. This study analyzed the impact of pre-transport holding times (one, three, and five days) with four replications and an average initial weight of 73.60 ± 12.53 g on the physiological condition and production performance of farming mud crabs in an apartment system. The crabs were transported dry from Muara Gembong, Bekasi Regency, West Java, to the IPB Fisheries and Marine Observation Station (IFMOS) Ancol, North Jakarta, DKI Jakarta, for three hours. The crabs were farming in apartment boxes with a recirculation system for 14 days. The results showed that the crabs experienced severe gill damage indicated by the lysis of gill cuticles and low survival rates, especially after five days of pre-transport holding. The crabs experienced stress in all treatments, as indicated by high glucose levels above 30 mg/dL. The best survival rate was found in the one-day pre-transport holding time, with a value of 87.50% at the holding location and 95% at the farming location. In conclusion, a one-day pre-transport holding time provides better physiological conditions and production performance for mud crab farming in an apartment system. Keywords: crab, gills, natural catch, stress ABSTRAK Budidaya kepiting bakau (Scylla serrata) di Indonesia umumnya menggunakan benih dari alam, yang ditangkap, ditampung, dan kemudian di transportasi kering ke lokasi budidaya. Penampungan kepiting berlangsung beberapa hari sambil menunggu konsumen. Penelitian ini menganalisis dampak lama waktu penampungan pratransportasi (satu, tiga, dan lima hari) dengan empat ulangan dan bobot rata-rata awal 73,60 ± 12,53 g, terhadap kondisi fisiologi dan kinerja produksi kepiting bakau yang dibudidayakan dalam sistem apartemen. Kepiting di transportasi kering dari Muara Gembong, Kabupaten Bekasi, Jawa Barat, ke IPB fisheries and marine observation station (IFMOS) Ancol, Jakarta Utara, DKI Jakarta, selama tiga jam. Kepiting dibudidayakan pada boks apartemen dengan sistem resirkulasi selama 14 hari. Hasil penelitian menunjukkan bahwa kepiting mengalami kerusakan insang yang parah ditunjukkan dengan lisisnya kutikula insang dan tingkat kelangsungan hidup rendah, terutama setelah lima hari lama penampungan. Kepiting mengalami stres dalam semua perlakuan, yang ditunjukkan oleh tingginya kadar glukosa di atas 30 mg/dL. Tingkat kelangsungan hidup terbaik yakni pada lama waktu penampungan satu hari, dengan nilai 87,50% di lokasi penampungan dan 95% di lokasi budidaya. Kesimpulannya, lama waktu penampungan satu hari pratransportasi memberikan kondisi fisiologi dan kinerja produksi budidaya kepiting bakau sistem apartemen yang lebih baik. Kata kunci: insang, kepiting, stres, tangkapan alam